Potensi fusarium non patogenik untuk mengendalikan fusarium oxysforum f. sp. cubense pada tanaman pisang barangan - Aulia Aghna; Lisnawita Muis; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2019)
Fusarium oxysforum f. sp. cubense (Foc) is one of the important pathogens causing fusarium wilt on banana plants. This pathogen reduces the productivity of banana plants and cause more than 35 % of dead banana plant. The disease management has been done from chemical control to biological control. The use of  Non Phatogenic Fusarium (FoNP) in some plants is quite effective in suppressing fusarium wilt disease. The aim of this research was to know the potency of FoNP isolates E3 and E5 (BALITTRO, Bogor) which were applied  on barangan cultivar ‘barangan’ to control fusarium wilt disease. The method of this research was Randomized Complete Design Factorial withtwo isolates of-FoNP; i.e. E5 and E3. Application was conducted by immersing the banana seeds with the fungal incolum. Conidia suspension (106 conidia/ ml) and FoNP methabolites were used, with or without pathogen with the following treatments: P1 : conidia suspension E5 with  Foc; P2 : conidia suspension E3 with Foc; P3 : conidia suspension E5 without Foc; P4 : conidia suspension E3 without Foc; P5 : metabolite E5 with Foc; P6 : metabolite E3 with Foc; P7 : metabolite E5 without Foc; P8: metabolite E3 with Foc; P9 : Foc; P10 : without Foc. The results showed that there weas no symptoms caused by Foc on leaves or banana herbs in the field. In the in vitro experiments, Non Pathogenic Fusarium isolates E5 and E3 could inhibit the growth of Foc with the inhibiting zone was 29. 16 % and 19. 22 % respectively. Keywords: Barangan Cultivar, Fusarium oxysforum f. sp. cubense, non pathogenic fusarium, fusarium wilt disease.